Being present: is it the most important communication skill? - Oktifani Winarti; Ratih Pandu Mustikasari; Hanna Nurhaqiqi; Valentin Cretto-Bergerat (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
The COVID-19 pandemic has made people rely on the presence of the internet to run their business. Businesses, schools, retail, religious gatherings, and other components are all required to use an internet platform in some way. People can meet face-to-face and the feature of the contact is reinforced by both verbal and non-verbal communication prior to the viral eruption, making conversation much easier. The goal of this study is to emphasize the importance of being present during the COVID-19 Pandemic as well as the future projection of presence post-pandemic. Being present, as before the pandemic, comes effortlessly without conscious reflection because the interaction takes place offline without any restrictions. This research is using a literature review by comparing and contrasting the previous studies and the result extend that being present is the most crucial communication skill; it is the most important and most challenging communication skill to have in this unprecedented times but arguably support an effective communication for various types of social interactions. it is also the foundation of communication and can aid in more effective engagement on all levels (perception, comprehension, reasoning, memory, and production).